Studi Kritik Sanad Terhadap Hadis Pada Jalur Ali Bin Abi Thalib Dalam Karya Musnad Ahmad Bin Hanbal - Ardi, Ardi; M, Bukhari; Muslim, Muslim (Institut Agama Islam Sumatera Barat Pariaman, 2024)
The Musnad of Ahmad ibn Hanbal is a phenomenal work as a book of hadith that compiles many traditions of the Prophet Muhammad. Scholars have pointed out that the Musnad contains many dhaif and maudhu' traditions. The purpose of this research is to reveal the sanad of traditions contained in the Musnad of Ahmad ibn Hanbal specializing in the sanad line of the tradition of Ali ibn Abi Talib as a sample. This research utilizes a qualitative method using library research with the nature of qualitative descriptive research. The findings of this research can be concluded that there are 16 hadith transmission lines of 'Ali b. Abi Talib. As a sample, this research took only 3 sanad lines, namely the 11th, 13th and 14th sanad lines. Based on this, there is a narrator who is majhul. From the 3 sanad lines studied, it contains 13 narrators, there are 7 narrators who are considered tsiqah and maqbul, and 6 narrators who are considered majhul. Therefore, it can be stated that the sanad of the hadith contained in the Musnad of Ahmad Ibn Hanbal is proven to have a dhaif sanad line.